Pertanggungjawaban terhadap Perbuatan Melawan Hukum oleh Tenaga Kesehatan yang Merugikan Pasien - I Nyoman Putu Budiartha; Luiza Klementina M Asa; I Gusti Agung Ayu Gita Pritayanti Dinar (Warmadewa Press, 2024)
Health workers are professionals in the medical field whose main responsibility is to provide high-quality medical services to patients using methods and approaches based on medical science and relevant ethical principles. However, judging from some of their practices, it is often found that there are acts against the law or malpractice. This is caused by the lack of knowledge and experience of health workers and negligence committed carelessly and intentionally, which is certainly not desired by the health workers themselves. The problems raised are: 1. How is the liability of unlawful acts by health workers against losses suffered by patients; 2. What are the causes of unlawful acts by health workers that harm patients? By using statutory and conceptual approaches, the research methodology is normative legal research. The findings of this study indicate that health professionals often violate the law because they are not aware of their own rights and obligations. Or there are elements of error and negligence and this can bring harm to the patient. Where in the liability of health workers can be responsible in accordance with the losses suffered by patients where liability is divided into administrative, civil and criminal liability.